2013
DOI: 10.1007/s10646-013-1153-y
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of root growth, acid invertase activity and transcript level to copper stress in two contrasting populations of Elsholtzia haichowensis

Abstract: The present study aimed to test a hypothesis that acid invertases in root of metallophytes might play important roles in root growth under heavy metal stress. Plants of two contrasting populations, one from an ancient Cu mine (MP) and the other from a non-contaminated site (NMP), of metallophyte Elsholtzia haichowensis were treated with Cu in controlled experiments. The results showed that MP was Cu tolerant under 10 μM Cu2+ treatment. Cu treatment resulted in a higher root/shoot biomass ratio in MP compared t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…Excess Cu ions in plants cause disturbances in photosynthesis, which can result in oxidative stress, with increasing reactive oxygen species (ROS), reducing carbon fixation, and reducing or inhibiting plant development (Küpper and Andresen 2016). Exposure to Cu stress leads to remodeling in root morphology (Cai et al 2014), since the root is the first organ to come into contact with the contaminant. The use of digital images of roots is an important parameter for analysis of root development.…”
Section: Introductionmentioning
confidence: 99%
“…Excess Cu ions in plants cause disturbances in photosynthesis, which can result in oxidative stress, with increasing reactive oxygen species (ROS), reducing carbon fixation, and reducing or inhibiting plant development (Küpper and Andresen 2016). Exposure to Cu stress leads to remodeling in root morphology (Cai et al 2014), since the root is the first organ to come into contact with the contaminant. The use of digital images of roots is an important parameter for analysis of root development.…”
Section: Introductionmentioning
confidence: 99%
“…The optimum temperature of GspInv was 45 • C. More than 50% of the protein activity was shown when tested at temperatures between 30 and 55 • C (Figure 3B). The optimum temperature and pH of GspInv were similar to most of the invertases from other fungi, with optimum temperature and pH of 40-70 • C and 4.5-6.5, respectively (Acosta et al, 2000;Cai et al, 2014;Nadeem et al, 2015).…”
Section: Gspinv Characterizationmentioning
confidence: 64%
“…E. haichowensis was proven to possess the exclusion strategy, comprising avoidance of metal uptake and restriction of metal transport to the shoots (Lou et al 2004;Song et al 2004). Its population from mine accumulated significantly lower Cu than that from none contaminated sites under Cu stress, thus possibly reducing the Cu exposure of invertases (Ke et al 2008;Cai et al 2014). Excess metal ions can be removed from the cytosol by efflux or compartmentation, which further reduce the Cu exposure of invertase.…”
Section: Discussionmentioning
confidence: 99%
“…It is proposed that acid invertases play a vital role in regulation of Suc transport and partitioning, sugar storage, cell differentiation and enlargement, as well as the response to various biotic and abiotic stresses such as wounding, cold, drought, pathogen infection, salinity and hypoxia (Sturm and Tang 1999;Roitsch and González 2004;Ruan et al 2010). Moreover, recent studies have shown that acid invertases were crucial for metallophyte plants to govern root growth and root/shoot biomass allocation, and at least partly associated with Cu tolerance by supplying carbon and energy for tolerance mechanisms (Stobrawa and LorencPlucińska 2007;Xiong et al 2008;Huang et al 2011;Cai et al 2013Cai et al , 2014.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation